Digital Preservation of Photojournalism Case Study of the Kompas Daily - Ratnawati, Sintha; Rahmawati, Yuli (Record and Library Journal, 2015)
Newspapers present information to the public on various topics, such as politics, economics, culture, and sports. Through its preaching, newspapers report a number of valuable events as historical records. Photos, complementing the news, come with a visual approach. Based on the rules of journalism, the photo meets the qualification as a reference source. Kompas Daily, published since June 28, 1965, immortalize various milestones in the work of photographs, stored in printed format, positive and negative, and digitized. Digitization becomes the preferred way to perpetuate the value contained in the printed photo work. Digitization is done for positive and negative photos taking into account the weight of journalism and the condition of the material. This activity is handled by Kompas Information Center through the process of media transfer, indexing, and synchronization. Two important issues to ensure optimization of the digitization result are metadata standardization and an integrated retrieval system. Metadata standardization is formulated based on guidelines developed specifically for the publishing industry, the IIM standard, combined with subjectÂ category modifications known as IPTC NewsCodes. Integrated retrieval systems are built to include the completeness of the source information of the publication as enrichment. This system connects to the full data of photo creation, storage procedure, and the mechanism of retrieval. The Information Lifecycle concept offers one more link, the utilization of digitization results to create new information.